PERMOHONAN DISPENSASI NIKAH DALAM PERSPEKTIF SADDU DZARI’AH - Ratno Asep Sujana (An-Nahdliyyah: Jurnal Studi Keislaman, 2023)
This research discusses the considerations of judges in granting marriage dispensation from the perspective of sadd al-dzari`ah. Marriage dispensation is a concession granted by the Religious Court to individuals who intend to marry but have not reached the legal age for marriage. One compelling reason for approving marriage dispensation is the pregnancy of an unmarried prospective bride. In other cases, there may be a close relationship between a man and a woman who is not of legal age to marry. If the marriage is not carried out, there is concern that actions forbidden by religious law may occur. In the second case, the judge considers the decision and approves it from the perspective of sadd al-dzari`ah, which aims to prevent actions that may lead to harm or damage. The purpose of this research is to enhance understanding related to marriage dispensation requests from the perspective of sadd al-dzari`ah. The research employs library research, involving the study of references such as books, articles, and internet browsing. The implications of Law Number 16 of 2019 on Amendments to Law Number 1 of 1974 concerning Marriage include a change in the legal age for marriage for women, which was raised from 16 to 19 years. However, in reality, many men and women below the legal age still apply for marriage dispensation. In this context, it becomes the duty of the Religious Court Judge to decide whether to approve or reject such marriage dispensation requests.